BASIC FACTORS AFFECTING THE QUALITY OF HUMAN CAPITAL - Bondarchuk , N.V. (The actual problems of regional economy development, 2018)
The article is devoted to the study of the determinants that influence the formation and development of human capital. It is suggested, under human capital, to understand the stock of professional and social competences (knowledge, skills, abilities) accumulated in the course of social and economic activity, professional experience, creative and mental abilities, motivation to work and self-development, mobility, adaptive ability, mental and physical well-being The moral values that contribute to economic activity, to the increase of labor productivity, lead to an increase in incomes, both of the individual and of society, of which he is. The basic properties of human capital are defined, among them: the ability to produce and increase incomes; accumulation and necessity of constant investing; physical and moral wear; Dependence on ways of motivation and stimulation; high risk; distance of return on investment in time; the dependence of the return on the intensity of the investment process and on the life expectancy of the carrier of human capital and its able-bodied period, etc. It is determined that many formal and informal social institutions influence the process of formation of human capital, namely: the system of compulsory school and vocational education, additional training in the concept of lifelong learning, family, society, and state. The main factors influencing the quality of human capital, among which are: investing in education, are outlined; professional development of employees; state of health care; social environment; demographic situation; living standards of the population; ecological situation; mobility of staff.